Impact of a Novel Preoperative Patient-centered Surgical Wellness Program. Issue 4 (October 2018) - Kelley, Kristen E.; Fajardo, Alyssa D.; Strange, Nancy M.; Harmon, Carol A.; Pawlecki, Kim; Sieber, Marnie; Walke, Nikki; Fadel, William F.; Wooden, William A.; Sadowski, Josh; Birdas, Thomas J.; Stevens, Larry H.; et al.
Abstract : Objective: The objective of this study was to evaluate if a preoperative wellness bundle significantly decreases the risk of hospital acquired infections (HAI). Background: HAI threaten patient outcomes and are a significant burden to the healthcare system. Preoperative wellness efforts may significantly decrease the risk of infections. Methods: A group of 12, 396 surgical patients received a wellness bundle in a roller bag during preoperative screening at an urban academic medical center. The wellness bundle consisted of a chlorhexidine bath solution, immuno-nutrition supplements, incentive spirometer, topical mupirocin for the nostrils, and smoking cessation information. Study staff performed structured patient interviews, observations, and standardized surveys at key intervals throughout the perioperative period. Statistics compare HAI outcomes of patients in the wellness program to a nonintervention group using the Fisher's exact test, logistic regression, and Poisson regression. Results: Patients in the nonintervention and intervention groups were similar in demographics, comorbidity, and type of operations. Compliance with each element was high (80% mupirocin, 72% immuno-nutrition, 71% chlorhexidine bath, 67% spirometer). The intervention group had statistically significant reductions in surgical site infections, Clostridium difficile, catheter associated urinary tract infections, and patient safety indicator 90. Conclusions: A novel, preoperative, patient-centered wellness program dramatically reduced HAI in surgical patients at an urban academic medical center.